Effect of Postoperative Constrictive Physiology on Early Outcomes after Off-Pump Coronary Artery Bypass Grafting - Kim, Jung-Hwan (Korean Society for Thoracic and Cardiovascular Surgery, 2013)
BACKGROUND: Constrictive pericarditis after coronary artery bypass surgery has been known to affect cardiac output by limiting diastolic ventricular filling. We aimed to assess the influence of postoperative constrictive physiology on the early outcomes of patients undergoing off-pump coronary artery bypass grafting (OPCAB). MATERIALS AND METHODS: Between January 2008 and July 2011, 903 patients underwent an isolated OPCAB and postoperative transthoracic-echocardiography. The patient cohort was classified into two groups: group A, constrictive physiology and group B, control group without constrictive physiology. Early outcomes were analyzed between the two groups. RESULTS: Of the total 903 patients, group A consisted of 153 patients (16.9%). The amount of blood loss in group A during the postoperative 24 hours was greater than that of group B, but this was not statistically significant (p=0.20). No significant differences were found in the mortality rates (group A, 0.6%; group B, 1.4%; p=0.40) and 30-day major adverse cardiac and cerebrovascular events (MACCEs; group A, 3.3%; group B, 6.1%; p=0.42). CONCLUSION: Postoperative constrictive physiology does not affect 30-day MACCEs or other major complications after OPCAB. The results of this study suggest that patients with early postoperative constrictive physiology do not need medical or surgical treatment, and that conservative care is sufficient.